Digital compensation for analog front-ends : a new approach to wireless transceiver design - Horlin, François (J. Wiley & Sons, 2008)
The desire to build lower cost analog front-ends has triggered interest in a new domain of research. Consequently the joint design of the analog front-end and of the digital baseband algorithms has become an important field of research. It enables the wir.